2020
DOI: 10.5863/1551-6776-25.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Adherence in Children With Sickle Cell Disease: A Single-Institution Experience

Abstract: OBJECTIVES The Advisory Committee on Immunization Practices (ACIP) recommends additional immunizations for people with asplenia or functional asplenia, such as children with sickle cell disease. Adherence rate to the recommended immunization schedule for functional asplenia remains low for children with sickle cell disease. The purpose of this study was to assess the immunization adherence for this population at a single institution in Kentucky and to evaluate the use of the Kentucky Immunization Registry (KYI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Studies have found that children with SCD have lower adherence to the immunization schedule for SCD‐specific vaccines than general vaccines 31,43 . This indicates a need for coordinated care between pediatricians and hematologists for children with SCD to help providers understand the importance of SCD‐specific vaccines and facilitate administration specifics on the supply and distribution of these vaccines 44 . Further, the introduction of new vaccines, such as the 15‐valent and 20‐valent pneumococcal conjugate vaccines, is expected to impact the UTD rates of pneumococcal vaccines 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that children with SCD have lower adherence to the immunization schedule for SCD‐specific vaccines than general vaccines 31,43 . This indicates a need for coordinated care between pediatricians and hematologists for children with SCD to help providers understand the importance of SCD‐specific vaccines and facilitate administration specifics on the supply and distribution of these vaccines 44 . Further, the introduction of new vaccines, such as the 15‐valent and 20‐valent pneumococcal conjugate vaccines, is expected to impact the UTD rates of pneumococcal vaccines 39 .…”
Section: Discussionmentioning
confidence: 99%
“…31,43 This indicates a need for coordinated care between pediatricians and hematologists for children with SCD to help providers understand the importance of SCD-specific vaccines and facilitate administration specifics on the supply and distribution of these vaccines. 44 Further, the introduction of new vaccines, such as the 15-valent and 20-valent pneumococcal conjugate vaccines, is expected to impact the UTD rates of pneumococcal vaccines. 39 Future research should explore the uptake and effects of these newly introduced vaccines on the population with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…However, US investigators have reported lower coverage estimates. A single‐center evaluation in Louisville, KY in 2017 indicated 52% of children with SCD adhered to influenza vaccination recommendations 35 . Similarly, an investigation among children with SCD referred to services in Indiana between 2009 and 2017 found that although 60% of children received at least one influenza vaccination, the annual proportion declined over time and was 33% by the end of the study period 36 .…”
Section: Discussionmentioning
confidence: 99%
“…14 In Kentucky, A 2020 study showed that only 6% of children with functional asplenia due to sickle cell disease having complete adherence to ACIP guidelines. 15 While 1 study in Michigan found increased compliance to PPSV23 vaccination in sickle cell patients, their rates were lower than state and national compliance rates. 7 In Louisiana, similar results were observed, as 59% of children did not receive the second dose of the pneumococcal vaccine.…”
Section: Research Has Shown That Low-income Populations Reportmentioning
confidence: 96%